PENGARUH KEBIJAKAN UTANG, LIKUIDITAS, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN YANG TERDAFTAR PADA INDEKS LQ-45 DI BEI PERIODE 2013-2016 - Zahratul Aziz Aini; Tri Kurniawati; Efni Cerya (Jurnal Ecogen, 2018)
Investors have a goal to get maximum returns by anticipating the impact they will face in the future. In this study the return meant is dividend policy. There are 4 factors that influence dividend policy, namely: (1) debt policy, (2) liquidity, (3) company size, (3) profitability. This type of research is causative with secondary data, where this study analyzes how the influence of one variable with another variable or how a variable affects other variables. The sampling technique in this study used a purposive sampling method. Purposive sampling is the determination of the cellphone and population based on the criteria desired by the researcher in order to obtain a representative sample according to the criteria. The object of this study is a company listed on the LQ-45 Index on the Indonesia Stock Exchange with a period of 2013-2016. The data analysis technique uses multiple linear regression analysis using SPSS version 21.0. The results of this study indicate that (1) debt policy has a negative and not significant effect on dividend policy in the LQ-45 index company listed on the Stock Exchange in 2013-2016, (2) liquidity has a negative and not significant effect on dividend policy on LQ-index companies 45 which are listed on the IDX in 2013-2016, (3) the size of the company has a negative and not significant effect on dividend policy on LQ-45 index companies listed on the Indonesia Stock Exchange in 2013-2016, and (4) Profitability has a negative and not significant effect on policy dividends on LQ-45 index companies listed on the Indonesia Stock Exchange in 2013-2016.Keyword: Dividend Policy, Debt Policy, Liquidity, Company Size, and Profitability